(3MGdI GdLRGFQ hGdOhd GdYQHjIs - (3MSjHI(B, (3eadGMs ((3GdLRGFQ(B:s (3OGQ CLjGd GdQbej (B,s)
(3jJfGhd gPG GdcJGH ehVhY ddhSGWI GdeGdjI GdeUQajI hZjQ GdeUQajI eY GdeNGWQ GdJj JhGLggG hWHjYI GdhSGWI GdeGdjI aj Shb GdChQGb GdeGdjI CjVG GdEONGQ hCOhGJ JYHFJg aj eDSSGJ GdhSGWI GdeGdjI hCNjQG OhQ GdhSGWI GdeGdjI aj JYHFI GdEONGQ aj GdLRGFQ hGdOhd GdYQHjI, ceG jYQV Cge GdJMOjGJ GdJj JhGLggG GdhSGWI GdeGdjI aj JYHFI GdGONGQ GdeJWdH efgG Ydi eSJhi GdhWf GdYQHj(B.s
(3HHdjhZQGajG(B: (3U U(B.251-265 (3edGMb(B: (3U(B269-275s
Keywords: (3GdChQGb GdeGdjIs; (3GdEONGQs; (3GdeGdjIs